Investigating Students’ Fear of Making Mistakes in English Speaking Performance in EFL Contexts at SMK PGRI Sumbermanjing - Syahrul Sidan Hafid; Agus Sholeh (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Fear of making mistakes is one of the psychological factors that may hinder students’ participation in English speaking activities. In vocational high school settings, speaking competence is particularly important because students are expected to communicate effectively in both academic and professional contexts. However, many learners remain reluctant to speak English due to concerns about making errors. Understanding this phenomenon is essential for supporting students’ oral language development. This study investigated students’ fear of making mistakes in English speaking performance at SMK PGRI Sumbermanjing, East Java, Indonesia. The study aimed to explore the factors contributing to students’ fear of making mistakes and examine how this fear affected their speaking performance in classroom activities. A qualitative case study design was employed. Twenty students were selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data were analyzed using thematic analysis to identify recurring patterns and themes. The findings revealed four major factors associated with students’ fear of making mistakes: fear of pronunciation errors, fear of negative evaluation from peers, limited vocabulary knowledge, and fear of teacher correction. These factors influenced students’ speaking performance by reducing confidence, increasing hesitation, limiting classroom participation, and encouraging avoidance of speaking opportunities. Fear of negative evaluation and pronunciation-related concerns were reported most frequently among participants. In conclusion, fear of making mistakes remains an important challenge affecting students’ English speaking performance. Creating supportive classroom environments and providing meaningful speaking opportunities may help students participate more confidently in English communication activities.